PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SICEPAT EKSPRES BATAM - Elzan Fazira; M. Khoiri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of discipline and work motivation on employee performance at PT SiCepat Ekspres in Batam. Quantitative research is a type of research with a population of 110 people. Questionnaire is an instrument used for data collection. The sampling technique used a saturated sample, meaning that all of the population was sampled. data processing using SPSS version 26 with the results of the study it is known that discipline has a arithmetic value > t table that is 3.424 > 1.65922 with a significance of 0.001 < 0.05 which means that discipline has a positive and significant effect on employee performance, while work motivation tcount > t table namely 6.062 > 1.65922 with a significance of 0.000 <0.05, which means that monkey motivation has a positive and significant effect on employee performance. And motivation and discipline together have a positive and significant effect on employee performance. This is indicated by the results of the F test with a value of (F count) 54,984 > 2.69 (F table) with a significance value of 0.000 < 0.05. And the value of R square is 0.507.